STUDI PREPARASI TIO2 NANOTUBE SERBUK DENGAN TEKNIK RAPID BREAKDOWN ANODIZATION - Linda J Kusumawardanil; Ivandini Tribidasari; Jarnuzi Gunlazuardi (Universitas Pakuan, 2016)
Technique of Rapid Breakdown Anodization (RBA) is the new anodisasi technique introduced in 2009 as super fast synthesis methods for producing TiO2 powder. The development of this technique continues to be done in order to obtain the best quality of TiO2 powders according to the needs of the application. At this time the experiment reported the existence of the influence the granting of potential anodisasi currently underway against TiO2 powder produced good particle size, surface area and shape of the morfologinya. In addition, observations on the reaction time is also conducted to take into account the efficiency. From the results of the experiment, potential variations below 20 V, i.e., 10, 13, 14 and 15 V, it can be reported that the plate It can be transformed into the perfect TiO2 powder on electrochemical reaction of potential system 15 V for approximately 3 hours in perchloric acid media 0.15 M. Whereas the process of potential reactions on 10, 13 and 14 V does not produce TiO2 powder significantly in the time of observation for 7 hours. So further study focused on the synthesis of TiO2 powder results in a potential 15 V which will be compared with the potential 20 V, which is a potential that is used when this technique was first introduced. From the results of the experiment, reported on the potential RBA engineering 15 V produces TiO2 powder with a size outer diameter are smaller, i.e. an average of 84 nm with a more uniform particle size and surface area of the Crystal results kalsinasi at 500oC generated on 15 potential V is wider with a more uniform morphology, i.e. 69.723 g/m2 compared to 20 V , i.e. 63.824 g/m2. This will provide a significant influence in the activity of the fotokatalitik used for the fotodegradasi, as well as its application as DSSC (Dye Sensitized Solar Cells).Â Â KeyWordÂ :Rapid Breakdown Anodization (RBA), Anodisasi, TiO2, TiO2 Nanotube-Serbuk